Ecological interactions and the fitness effect of water‐use efficiency: Competition and drought alter the impact of natural MPK12 alleles in Arabidopsis. (11th February 2016) - Campitelli, Brandon E.; Des Marais, David L.; Juenger, Thomas E.
Abstract: The presence of substantial genetic variation for water‐use efficiency (WUE) suggests that natural selection plays a role in maintaining alleles that affect WUE. Soil water deficit can reduce plant survival, and is likely to impose selection to increase WUE, whereas competition for resources may select for decreased WUE to ensure water acquisition. We tested the fitness consequences of natural allelic variation in a single gene ( MPK12 ) that influences WUE in Arabidopsis, using transgenic lines contrasting in MPK12 alleles, under four treatments; drought/competition, drought/no competition, well‐watered/competition, well‐watered/no competition. Results revealed an allele × environment interaction: Low WUE plants performed better in competition, resulting from increased resource consumption. Contrastingly, high WUE individuals performed better in no competition, irrespective of water availability, presumably from enhanced water conservation and nitrogen acquisition. Our findings suggest that selection can influence MPK12 evolution, and represents the first assessment of plant fitness resulting from natural allelic variation at a single locus affecting WUE.